An ATF4-ATG5 signaling in hypothalamic POMC neurons regulates obesity. Issue 6 (3rd June 2017) - Xiao, Yuzhong; Deng, Yalan; Yuan, Feixiang; Xia, Tingting; Liu, Hao; Li, Zhigang; Chen, Shanghai; Liu, Zhixue; Ying, Hao; Liu, Yi; Zhai, Qiwei; Guo, Feifan
ABSTRACT: ATF4 (activating transcription factor 4) is an important transcription factor that has many biological functions, while its role in hypothalamic POMC (pro-opiomelanocortin-α) neurons in the regulation of energy homeostasis has not been explored. We recently discovered that mice with an Atf4 deletion specific to POMC neurons (PAKO mice) are lean and have higher energy expenditure. Furthermore, these mice are resistant to high-fat diet (HFD)-induced obesity and obesity-related metabolic disorders. Mechanistically, we found the expression of ATG5 (autophagy-related 5) is upregulated in POMC neurons of PAKO mice, and ATF4 regulates ATG5 expression by binding directly to its promoter. Mice with Atf4 and Atg5 double knockout in POMC neurons have reduced energy expenditure and gain more fat mass compared with PAKO mice under a HFD. Finally, the effect of Atf4 knockout in POMC neurons is possibly mediated by enhanced ATG5-dependent macroautophagy/autophagy and α-melanocyte-stimulating hormone (α-MSH) production in the hypothalamus. Together, this work not only identifies a beneficial role for ATF4 in hypothalamic POMC neurons in the regulation of obesity, but also provides a new potential therapeutic target for obesity and obesity-related metabolic diseases.